2011
DOI: 10.1007/s13258-010-0127-1
|View full text |Cite
|
Sign up to set email alerts
|

Molecular cloning, chromosomal localization and expression profiling of porcine selenoprotein M gene

Abstract: Selenoprotein M may regulate a myriad of biological processes through its redox function. In pigs, neither the nucleotide sequence nor the amino acid sequence is known. Furthermore, patterns of tissue expression and regulation by dietary selenium (Se) have not been examined. We determined the full coding sequence (CDS) and the chromosomal location of the porcine gene, SELM, and described its expression profile in vivo under different dietary Se concentrations. The cDNA sequence of porcine SELM from the start c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 21 publications
1
11
0
2
Order By: Relevance
“…The observed highly homology of SelM indicates that chicken SelM was derived from a common ancestor. Our 3D structural analysis demonstrated that chicken SelM was similar to that of pig SelM [9], chicken SelW [10,11], and chicken SelT [12], suggesting that they might exhibit similar functions.…”
Section: Discussionmentioning
confidence: 70%
See 4 more Smart Citations
“…The observed highly homology of SelM indicates that chicken SelM was derived from a common ancestor. Our 3D structural analysis demonstrated that chicken SelM was similar to that of pig SelM [9], chicken SelW [10,11], and chicken SelT [12], suggesting that they might exhibit similar functions.…”
Section: Discussionmentioning
confidence: 70%
“…However, the substitution of adenosines (A) for cytidines (C) shows no observable effect on Sec insertion into SelM. Pervious study has demonstrated that the SECIS element with -CC-motif appears to be universal in the Selm genes of mammalian animals [9]. In order to understand the evolutionary meaning of forms and motifs in the Selm SECIS element, we did a phylogenetic analysis encompassing a greater number of species.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations